Effectiveness of fundamental resonant frequency for determining the elastic properties of Argentinean Eucalyptus grandis in structural sizes - Piter, Juan Carlos Jesús (2004)
The present paper reports the results of an investigation regarding the elastic properties of Argentinean Eucalyptus grandis by the dynamic method of measuring the fundamental frequencies of vibration. It aims at scrutinising how that method is suitable to this timber species. For this purpose an empirical research project with one sample of boards and four samples of beams in structural sizes exhibiting a wide range of variation in quality was carried out. The results give evidence of the effectiveness of this method for determining the elastic properties for Argentinean Eucalyptus grandis in different sizes, and that it is reliable for pieces of high quality as well as for those containing important strength and stiffness reducing factors, such as the presence of pith, among others.